1997
DOI: 10.1172/jci119411
|View full text |Cite
|
Sign up to set email alerts
|

Identification of rat yolk sac target protein of teratogenic antibodies, gp280, as intrinsic factor-cobalamin receptor.

Abstract: Previous studies in the rat have shown that antibodies to gp280, a protein Ͼ 200 kD and closely associated with the early endocytic system can induce fetal malformations. Although gp280 is thought to act as a receptor, its ligand(s) is not known. In the current study, we report that purified gp280 from rat kidney, like the intrinsic factor-Cobalamin receptor (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
70
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(73 citation statements)
references
References 26 publications
2
70
0
1
Order By: Relevance
“…16 Indirect evidence for cubilin playing a similar role in ligand transcytosis comes from findings showing that albumin is transcytosed back to circulation via the proximal tubule epithelium, [17][18][19] as well as the fact that cubilin-mediated uptake of intrinsic factor-B 12 complex in the gut leads to its release into blood in the form of transcobalamin-B 12 . 20 Whether or not renal cubilin-mediated uptake of apoA-I and albumin from the glomerular filtrate might be part of a salvage process that affects levels of these proteins in the blood is not known. Here, we sought to define the relationships between genetic cubilin deficiency and renal uptake/urinary loss of apoA-I and albumin, along with the extent to which cubilin deficiency influences blood levels of each constituent, as well as HDL.…”
mentioning
confidence: 99%
“…16 Indirect evidence for cubilin playing a similar role in ligand transcytosis comes from findings showing that albumin is transcytosed back to circulation via the proximal tubule epithelium, [17][18][19] as well as the fact that cubilin-mediated uptake of intrinsic factor-B 12 complex in the gut leads to its release into blood in the form of transcobalamin-B 12 . 20 Whether or not renal cubilin-mediated uptake of apoA-I and albumin from the glomerular filtrate might be part of a salvage process that affects levels of these proteins in the blood is not known. Here, we sought to define the relationships between genetic cubilin deficiency and renal uptake/urinary loss of apoA-I and albumin, along with the extent to which cubilin deficiency influences blood levels of each constituent, as well as HDL.…”
mentioning
confidence: 99%
“…C ubilin, which is also known as the intrinsic factorcobalamin (IF-B12) receptor (1), is a multiligand receptor expressed at the apical plasma membrane and in endocytic compartments of several absorptive epithelia, especially the kidney proximal tubule, the small intestine, and the visceral yolk sac, where it plays a scavenger receptor function, in concert with megalin (2)(3)(4)(5). Mutations in the cubilin gene have been identified in a group of patients who have Imerslund-Gräsbeck's syndrome (or megaloblastic anemia type 1) (6,7), a rare genetic disorder characterized by defective intestinal absorption of vitamin B 12 and proteinuria.…”
mentioning
confidence: 99%
“…In this earlier work, it was found that antibodies raised against yolk sac or kidney and administered to pregnant rats (27) or anti-p400 against mouse cubilin administered to pregnant mice 2 during the period of organogenesis resulted in severe fetal abnormalities and death. Although the mechanism responsible for the pathological effect of the antibodies is unknown, they localized in yolk sac epithelium, possibly inhibiting the endocytic apparatus in those cells (25)(26)(27). Since rodent yolk sac is the major portal for maternalfetal exchange prior to development of chorioallantoic circulation (28), it is presumed that disruption of transport of nutrients, such as maternal serum proteins, vitamin B 12 , and cholesterol-containing lipoproteins, during the critical phase of organogenesis could be involved (12,25,29).…”
Section: Discussionmentioning
confidence: 99%